GAMBARAN KONSEP DIRI PENDERITA KUSTA DI KABUPATEN INDRAMAYU (DESCRIPTION OF LEPROSY PATIENTS SELF-CONCEPT IN INDRAMAYU REGENCY) - Kamsari, Kamsari; Carsita, Wenny Nugrahati; Aeni, Wiwin Nur (Journal of Nursing Care and Biomoleculer, 2019)
Introduction:Leprosy is an infectious disease that is a health problem both in Indonesia and the world. Indonesia is a country endemic to leprosy and is one of the countries with the highest cases of leprosy in the world. Leprosy causes problems for patients both physically, psychologically and socially. Late handling of leprosy will result in disability. The existence of the disability will result in decreased productivity. In addition to physical problems, social problems caused by leprosy in the community are still very large, including sufferers who have disabilities experience isolation by the community. The existence of such a isolation results in patients being reluctant to take medication that will have an impact on the transmission of the disease to their families and people closest to them. This will affect the patient's self-concept. The purpose of this study was to determine the self-concept of leprosy patients in Indramayu Regency. Method: This study used a quantitative design with a descriptive approach. The sample in this study was 84 leprosy patients. Result and Analysis: The results showed that 50% of leprosy patients had negative self-identities, 53.6% had negative body image, 63.1% had negative role models, 53.6% had negative self-ideals, and 51.2% had negative self-esteem. As many as 56% of people affected by leprosy in Indramayu Regency have a negative self-concept. Discussion: It is expected that the self-concept of leprosy patients increases with the assistance in the form of counseling to find out problems and make appropriate action plans for leprosy patients.